KEPASTIAN HUKUM PENYELESAIAN KONFLIK INTERNAL PARTAI POLITIK BERDASAR UU NO 2 TAHUN 2011 - Ahmad Zairudin (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
The design of internal party dispute arrangements has actually been regulated in Law Number 2 of 2011 concerningg political parties, this rule is a middle way to create regulation that can resolve internal dispute probmlems within political parties. It is hoped that this presence will be able to solve all problems within political parties that have legal certainty. There are saveral legal mechanisment disputes, including though political party courts, general courts and state administrative courts. This research Method uses normative juridical cocepts with statutory, case and conseptual approches. As for this study, researchers us sources of lega; materials in the form of primary legal materials, secondary legal materials and tertiary legal materials.